Unilateral Tax Policy in the Open Economy - Miriam Kohl; Philipp M. Richter (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper examines the effects of a unilateral reform of the redistribution policy in an economy open to international trade. We set up a general equilibrium trade model with heterogeneous agents allowing for country asymmetries. We show that under international trade compared to autarky, a unilateral tax increase leads to a less pronounced decline in aggregate real income in the reforming country, while income inequality is reduced to a larger extent for sufficiently small initial tax rates. We highlight as a key mechanism a tax-induced reduction in the market size of the reforming country relative to its trading partner, resulting in a firm selection effect towards exporting. From the perspective of a non-reforming trading partner, the unilateral redistribution policy reform resembles a unilateral increase in trade costs leading to a deterioration of terms-of-trade and a decline in both aggregate real income and inequality.
Keywords: D31; F12; F16; H24; 330; income inequality; redistribution; international trade; heterogeneous firms